Mindfulness Intervention for Stress Eating to Reduce Cortisol and Abdominal Fat among Overweight and Obese Women: An Exploratory Randomized Controlled Study. (2nd October 2011) - Daubenmier, Jennifer; Kristeller, Jean; Hecht, Frederick M.; Maninger, Nicole; Kuwata, Margaret; Jhaveri, Kinnari; Lustig, Robert H.; Kemeny, Margaret; Karan, Lori; Epel, Elissa
Abstract : Psychological distress and elevated cortisol secretion promote abdominal fat, a feature of the Metabolic Syndrome. Effects of stress reduction interventions on abdominal fat are unknown. Forty-seven overweight/obese women (mean BMI = 31.2 ) were randomly assigned to a 4-month intervention or waitlist group to explore effects of a mindfulness program for stress eating. We assessed mindfulness, psychological distress, eating behavior, weight, cortisol awakening response (CAR), and abdominal fat (by dual-energy X-ray absorptiometry) pre- and posttreatment. Treatment participants improved in mindfulness, anxiety, and external-based eating compared to control participants. Groups did not differ on average CAR, weight, or abdominal fat over time. However, obese treatment participants showed significant reductions in CAR and maintained body weight, while obese control participants had stable CAR and gained weight. Improvements in mindfulness, chronic stress, and CAR were associated with reductions in abdominal fat. This proof of concept study suggests that mindfulness training shows promise for improving eating patterns and the CAR, which may reduce abdominal fat over time.